Okak from the land (1900)
This is a copy print of a photograph of the mission at Okak. It provides a view of the mission buildings and wharf including a steamship in the harbour, circa 1900. This is a copy print of a photograph of the mission at Okak. It provides a view of the mission buildings and wharf including a steamship in the harbour, circa 1900.